Contação de história no mundo infantil: olhares e contribuições da pedagogia Piagetiana e Freinetiana - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2024)
This article aims to debate storytelling, understood as one of the main tools for reconstructing collective school daily life. We live in a world in which individuality is on the rise in all social spaces, in addition to a very intense electronic experience in school environments, which has made the acquisition of academic knowledge difficult. To support our discussion, we brought legal aspects that support early childhood education and children's rights. The importance of the school subject as a historical being with rights is understood, and is therefore capable of overcoming the aforementioned difficulties. We will dialogue with authors such as Jean Piaget and Célestin Freinet, who are important references in the area of education, presenting their contributions and their relationships with storytelling, addressing their reasons, the importance of this practice and the methodologies they proposed for the children's school space.
Keywords: Contação de história; Educação Infantil; Espaço Escolar; CNPQ:: CIÊNCIAS HUMANAS